Los costos históricos de producción y su incidencia en el estado de resultado integral - Chamba Salazar, Teresa Isabel (2017)
The changing environment in our country as well as technological progress require companies to seek new instruments of progress and management to position themselves in an appropriate market, for which the owners of the company INTRANSFORMAN S.A. require a broad view on how to determine your information, to get results, management must know if you want to reform or implement certain productive or administrative process. This thesis covers on the proposed implementation of a cost system for production orders which aims to establish conveniently and accurately the cost of production of each product manufactured by INTRANSFORMAN S.A…..